The class - Segal, Eric. (b, 1986)
The ethos and glamour of Harvard resonate throughout this story of five men--Andrew Eliot, Daniel Rossi, Ted Lambros, Jason Gilbert, and George Keller--from their first days at Harvard through their twenty-fifth class reunion.
Keywords: Class reunions -- Fiction; Harvard University -- Fiction; College graduates -- Fiction